PENGARUH KONSERVATISME AKUNTANSI, ASIMETRI INFORMASI, KUALITAS AUDIT, LEVERAGE, DAN PROFITABILITAS TERHADAP COST OF EQUITY - Titi Indri; Kenny Ardillah (Journal of Economic, Bussines and Accounting (COSTING), 2026)
This study investigates the effects of accounting conservatism, information asymmetry, Audit Quality, Leverage, and profitability on the cost of equity of financial sector companies listed on the Indonesia Stock Exchange (IDX) during 2020–2024. Using a quantitative approach with purposive sampling, 90 companies were selected, producing 450 firm-year observations from annual reports. Panel data regression analysis was conducted using EViews 13, including model selection, classical assumption testing, hypothesis testing, and coefficient of determination analysis. The findings indicate that, individually, only Audit Quality has a significant positive effect on the cost of equity, whereas accounting conservatism, information asymmetry, Leverage, and profitability show no significant influence. Collectively, the independent variables significantly explain variations in the cost of equity, with an Adjusted R² of 65.97%. These results suggest that investors place greater emphasis on Audit Quality than other financial indicators when assessing required returns in Indonesia's highly regulated financial sector.